Deformable Organic Nanowire Field‐Effect Transistors. Issue 7 (8th January 2018) - Lee, Yeongjun; Oh, Jin Young; Kim, Taeho Roy; Gu, Xiaodan; Kim, Yeongin; Wang, Ging‐Ji Nathan; Wu, Hung‐Chin; Pfattner, Raphael; To, John W. F.; Katsumata, Toru; Son, Donghee; Kang, Jiheong; et al.
Abstract: Deformable electronic devices that are impervious to mechanical influence when mounted on surfaces of dynamically changing soft matters have great potential for next‐generation implantable bioelectronic devices. Here, deformable field‐effect transistors (FETs) composed of single organic nanowires (NWs) as the semiconductor are presented. The NWs are composed of fused thiophene diketopyrrolopyrrole based polymer semiconductor and high‐molecular‐weight polyethylene oxide as both the molecular binder and deformability enhancer. The obtained transistors show high field‐effect mobility >8 cm 2 V −1 s −1 with poly(vinylidenefluoride‐ co ‐trifluoroethylene) polymer dielectric and can easily be deformed by applied strains (both 100% tensile and compressive strains). The electrical reliability and mechanical durability of the NWs can be significantly enhanced by forming serpentine‐like structures of the NWs. Remarkably, the fully deformable NW FETs withstand 3D volume changes (>1700% and reverting back to original state) of a rubber balloon with constant current output, on the surface of which it is attached. The deformable transistors can robustly operate without noticeable degradation on a mechanically dynamic soft matter surface, e.g., a pulsating balloon (pulse rate: 40 min −1 (0.67 Hz) and 40% volume expansion) that mimics a beating heart, which underscores its potential for future biomedical applications. Abstract : Deformable organic nanowire (NW) field‐effect transistors (FETs) with mechanical reliability are demonstrated with highly ductile and deformable NWs as the semiconductor. The NWs maintain a continuous structure under 100% strain in both channel length and width directions of the transistors. Stretchable FETs with single NWs are operated stably on a 3D soft matter substrate with dynamic volume expansion and contraction that mimics a beating heart.